“Pengembangan E-modul KPK dan FPB Berbasis Realistic Mathematics Education untuk Meningkatkan Motivasi Belajar Siswa Kelas IV SDN Karang Anyar 03 Pagi Jakarta Pusat” - Salsabila Dwi Safitry; Rossi Iskandar (Departement of Mathematics Education, 2023)
The purpose of this research and development is to produce a learning design product that can be used as an alternative for students, which can be used for independent learning, so that it can increase student learning motivation in class, namely E-modules. This research and development was carried out at SDN Karang Anyar 03 Pagi, Central Jakarta. This research and development uses the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. Learning Mathematics with a Realistic Mathematics Education approach that places a problem in Mathematics Learning in the daily life of students, so that it can make it easier for students to receive material and provide direct experience with individual student experiences. The eligibility of design experts is 83% in the feasible category, the eligibility of linguists is 96% in the feasible category, the eligibility of material experts is 95% in the feasible category, and the effectiveness of the pretest with a score Based on the overall results by the validator and students declared feasible to be implemented in the learning process students independently.